FISCAL SUSTAINABILITY IN INDONESIA: A FISCAL REACTION FUNCTION APPRACH - Dewana Pinasthika Lestari; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This paper investigate to the fiscal sustainability condition in Indonesia by analyzing the influence of government debt to GDP ratio on the primary balance ratio for the period of 1990 – 2022. Therefore, this study analyzed the data using the Vector Error Correction Model (VECM) method. The result show that the government debt during the period of 1990 – 2022 is in a safe position in the long run. In this case, the government is able to achieve a primary surplus condition, reducing the government’s financial risks. The primary surplus can reduce dependence on new debt. In other words, the government is able to control the growth of its debt proportionally to the country’s economy even amidst the Covid – 19 pandemic.